Подставная фигура: [роман] / Данил Корецкий - Корецкий Данил Аркадьевич (Черная кошка, 2000)
Экземпляры: ф.6 (20171218) / Инвентарный номер: 2151 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 66 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44